Scientific interpretation of geological statements in the Quran: plate tectonics and stabilizers - Jalal Bashirov (Opuscula Theologica et Scientifica)
This study examines the Quranic verse, "And the land we extended it, and placed in it stabilizers," through a geological lens, challenging claims of scientific inaccuracies. It argues that the verse aligns with modern geological concepts such as plate tectonics, ocean floor expansion, and the breakup of Pangea. Additionally, the role of stabilizers, including mountains and isostasy, is explored to highlight their compatibility with scientific principles. The study concludes that these verses, expressed in accessible language over 1,400 years ago, reflect profound scientific insight, supporting the Quran's claim as a divine revelation.